IMPACT OF DIFFERENT DOSES OF GAMMA IRRADIATION AND ETHYL METHANE SULPHONATE (EMS) ON PLANT GROWTH AND BULB YIELD OF ONION (Allium cepa L.) - Ghosh Shompa Rani; Hossain Md. Mokter; Islam Md. Rofiqul; Md. Nazmul Hasan Mehedi (Acta Scientifica Malaysia)
This study was conducted at Bangladesh Institute of Nuclear Agriculture (BINA) research farm, Mymensingh during November 2021 to March 2022 to evaluate the effect of gamma irradiation and chemical mutagen on growth and yield of onion. The experiment was laid out in randomized complete block design with three replicates and nine (9) treatments viz. four gamma irradiation doses (GD50, GD100, GD150, GD200) and four Ethyl Methane Sulphonate (EMS) doses (ED0.1%, ED0.3%, ED0.5%, ED0.7%) and control. The results showed that almost all the parameter studied were significantly influenced by the treatments. The highest germination 90.16%, survivability 94.33%, SCMR value 63.56μmol/ms, Total Soluble Solids (TSS) 15.10 %Brix were recorded in T1(GD50) treatment and the maximum mortality 67% in T7(ED0.5%), shoot length 17.18 cm in T5(ED0.1%), root length (3.35 cm) in T5(0.1%), neck diameter 1.06cm in T8 (ED0.7%), bulb diameter 5.36 in T4(GD200), plant height 70 cm in T4(GD200), single bulb weight 75g in T4(GD200) and fresh yield 24t/ha in T5(ED0.1%,). The minimum germination 8.33% in T3(GD150), survivability 36.66% in T8(ED0.07%), mortality 5.66% in T1 (GD50), shoot length 8.26cm in T3(GD150), root length 0.9 cm in T4 , SCMR value 55.26 μmol/ms in T2 (GD100 ), plant height 51cm in T3(GD150), bulb diameter 3.91 cm in T7(ED0.5) , neck diameter 0.84cm in T6 , single bulb weight 42g in T7 (ED0.5 ), fresh yield 1.5t/ha in T3(GD150 ), TSS 10.40 %Brix in T7 (ED0.5%) were observed. Gamma irradiation GD200 (T4) and EMS 0.1% (T5) performed superior considering growth and yield of onion.